2006
DOI: 10.1021/ef060258w
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the Problem of Loss-in-Capacity of Calcium Oxide in CO2Capture

Abstract: Calcium oxide has been identified to be one of the best candidates for CO 2 capture in zero-emission powergeneration systems. However, it suffers a well-known problem of loss-in-capacity (i.e., its capacity of CO 2 capture decreases after it undergoes cycles of carbonation/decarbonation). This problem is a potential obstacle to the adoption of the new technologies. This paper proposes a method of fabricating a CaO-based adsorbent without the problem of loss-in-capacity. An adsorbent was fabricated using the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 15 publications
2
73
1
Order By: Relevance
“…The sintering effect is profound in fluidized bed reactors, where the attrition of the catalysts particles is intensified [14], whereas in plug-flow reactors sintering could be caused by unstable heating rates and prolonged calcination times [25]. The reduction in CO2 adsorptive capacity could be overcome by introducing to the structure of CaO some small cations, for example Al 3+ [27] or supporting CaO on -alumina [28]. However, this strategy will lead to the increase in the catalysts costs.…”
Section: Carbon Capture and Storage Technologiesmentioning
confidence: 99%
“…The sintering effect is profound in fluidized bed reactors, where the attrition of the catalysts particles is intensified [14], whereas in plug-flow reactors sintering could be caused by unstable heating rates and prolonged calcination times [25]. The reduction in CO2 adsorptive capacity could be overcome by introducing to the structure of CaO some small cations, for example Al 3+ [27] or supporting CaO on -alumina [28]. However, this strategy will lead to the increase in the catalysts costs.…”
Section: Carbon Capture and Storage Technologiesmentioning
confidence: 99%
“…Previous studies (Li et al, 2005Feng et al, 2006), have reported promising materials, with a reasonably stable uptake of CO 2 ; they were obtained by mixing calcium oxide on the molecular level with an inert supporting material, with a high melting point, such as Al 2 O 3 , MgO, or TiO 2 . Our work concentrated on two ways of achieving truly mixed oxides, using CaO as the reactive phase.…”
Section: Preparation Of Sorbentsmentioning
confidence: 99%
“…[12] The loss in capacity is due in part from an intractable build up of oxide crystallites which effectively decreases the reactive surface area for CO 2 . [15] Solid amine-sorbents work in much the same way as aqueous amine systems, but with much lower water and hence potentially lower energy requirements. A number of aminemodified materials have been examined for reversible CO 2 adsorption/desorption behavior, however, the bulk of them suffer from low CO 2 capacities, instability during cycling, high temperature requirements, and are prohibitively expensive for more general use.…”
Section: Solid Sorbentsmentioning
confidence: 99%